Cognitive mechanisms of insight: The role of heuristics and representational change in solving the eight-coin problem - Öllinger, Michael; Jones, Gary; Danek, Amory H.; Knoblich, Günther (Journal of experimental psychology. Learning, memory, and cognition, 2013)
The 8-coin insight problem requires the problem solver to move 2 coins so that each coin touches exactly 3 others. Ormerod, MacGregor, and Chronicle (2002) explained differences in task performance across different versions of the 8-coin problem using the availability of particular moves in a 2-dimensional search space. We explored 2 further explanations by developing 6 new versions of the 8-coin problem in order to investigate the influence of grouping and self-imposed constraints on solutions. The results identified 2 sources of problem difficulty: first, the necessity to overcome the constraint that a solution can be found in 2-dimensional space and, second, the necessity to decompose perceptual groupings. A detailed move analysis suggested that the selection of moves was driven by the established representation rather than the application of the appropriate heuristics. Both results support the assumptions of representational change theory (Ohlsson, 1992). (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Gesehen am 03.12.2024